Tren Penelitian Artificial Intelligence (Kecerdasan Buatan) di Pendidikan Kejuruan: Analisis Konten - Mohamad Riyandi Badu; Jefri Aldo; Hafid Rahmandan; Esta Larosa; Musfir Rizal Pratama; Uci Trisnawaty Habi; Rahmat Hidayat Dongka (Universitas Negeri Gorontalo, 2024)
This article aims to analyze the development of Artificial Intelligence (AI) research in the context of vocational education. The study employs content analysis, evaluating vocational education journals sourced from the Sinta database. The research findings indicate that AI research in vocational education remains limited. Its applications in vocational education include the development of information systems and websites, learning media, improvements in the learning process, learning strategies, and assessment methods.